Commentaire sur le Manuel d'Epictète - Simplicius, of Cilicia. (Philosophia Antiqua, 1996)
The significance of Simplicius' commentary lies in the fact that it is a Neoplatonist interpretation of a Stoic text. This volume presents the first critical edition based on all the known manuscripts of this work and offers, in contrast to the edition of Schweighäuser (1800) and the recapitulation of this edition by Dübner (1840), a text which is more complete and improved. A long introduction places the work in the philosophical and historical context of its time and characterises it as a spiritual exercise. The edition is preceded by a summary of the history of the text.